Detection and phylogenetic profiling of the RNA2 fragments of noda virus associated with white tail disease in Malaysian Macrobrachium rosenbergii de man by RT-PCR - Saedi, Tayebeh Azam (2011)
The detection of nodavirus using RT-PCR and histopathological assay was carried out in Malaysian Macrobrachium rosenbergii. Nodaviruses, which were originally isolated from insects, are small non enveloped riboviruses with two single-stranded RNA genomes, RNA1 and RNA2. The 3.1 kb RNA1 gene encodes the RNAdependent RNA polymerase and the 1.4 kb RNA2 gene encodes the coat protein. The giant fresh water prawn, M. rosenbergii, locally known in Malaysia as ‘Udang Galah’ is widely distributed in most of the tropical and subtropical regions worldwide. The popularity of this prawn has grown rapidly and its demand as food is getting progressively greater. However, wild stocks of M. rosenbergii have seen declines in recent years as they are threatened by over fishing and diseases. Serious outbreaks of diseases in udang galah farms in Malaysia have resulted in high mortality rates. One of the new viral diseases in M. rosenbergii is white tail disease (WTD). Two viruses, M. rosenbergii nodavirus (MrNV) and extra small virus (XSV) have been found to be responsible for this disease. The RT-PCR method was used to detect the 650 bp and the 1114 bp fragments of the RNA2 of MrNV in infected samples. However, the presence of the XSV RNA was detected in two samples of the MrNV- positive samples. Partial nucleotide sequence analysis of the Malaysian isolates showed 98% nucleotide identity with the reported sequence of MrNV isolate from China (AY231437.2). The pathology of the disease was also investigated where progressive myofiber degeneration of the tail muscles, liquifactive myopathy, muscle fiber, fragmentation, granulation, and hemocyte infiltration were observed in the RT-PCRpositive samples for MrNV.